Evaluating the Effects of Process Variables on Protease-loaded Nano-liposome Production by Plackett-Burman Design for Utilizing in Cheese Ripening Acceleration - Jahadi, M.; Khosravi-Darani, K.; Ehsani, M.R.; Mozafari, M.R.; Saboury, A.A.; Seydahmadian, F.; Vafabakhsh, Z. (Asian Journal of Chemistry, 2012)
Placket-Burman design was applied to evaluate the impacts of physicochemical parameters on multicomponent nano-liposomal formulations of protease. Liposomes (lecithin: cholesterol) were prepared by heating method without employing any toxic solvent or detergent. The aim of the present study was screening the effects of eleven factors including the pH, the cholesterol/ lecithin ratio (w/w), the powder form food grade lecithin proportion (Ultralec®P) (% w/w), the enzyme/lecithin ratio (w/w), the stirring time (min), the process temperature (ºC), the speed of stirrer (rpm), the rate of stirrer diameter/tank diameter, the homogenization, the way of adding enzyme and the centrifugation conditions on the encapsulation efficiency (EE %) of nano-liposome. This nano-liposome was prepared according to 11-factor 12-run statistical model. The results showed that the lecithin (Ultralec®P) proportion, the rate of stirrer/tank diameter, the enzyme/lecithin ratio, the cholesterol/lecithin ratio (w/w), the speed of stirrer (rpm), the stirring time, the process temperature had significantly effect on encapsulation efficiency (EE %) (p < 0.05). The mean diameter and polydispersity index of successful formulation of flavourzyme-loaded liposome was 178 nm and 0.2 respectively.